Antifungal activity of selected lactic acid bacteria from olive drupes. (April 2023) - Riolo, Mario; Luz, Carlos; Santilli, Elena; Meca, Giuseppe; Cacciola, Santa Olga
Abstract: In this study, 16 Lactobacilli (LABs) isolated from the drupes of olive ( Olea europaea ) oil varieties were identified as Lactiplantibacillus plantarum (seven isolates), Pediococcus pentosaceus (six isolates), Enterococcus faecium (two isolates) and Streptococcus salivarius (a single isolate) by peptide mass fingerprinting and sequencing of the 16S rRNA. Antifungal activity of LABs and their cell-free fermentates (CFSs) against several plant pathogenic fungi and oomycetes (fungi sensu lato ), including Alternaria, Aspergillus Colletotrichum, Penicillium, Plenodomus and Phytophthora, was evaluated in vitro using the culture overlaying and the agar diffusion tests. Minimal inhibitory concentration (MIC) and minimal fungicidal concentration (MFC) were determined. LABs showed antifungal activity against the fungi sensu lato tested. The most noticeable inhibitory activity was shown by isolates of L. plantarum and P. pentosaceus against Fusarium oxysporum, Colletotrichum species and Penicillium nordicum . Chemical analysis revealed CFSs contained acid lactic and variable quantities of 14 diverse phenolic acids and 26 volatile organic compounds (VOCs). No obvious correlation was found between the metabolic profile of LABs and their antifungal efficacy. However, it is the first time that the potential of fermentates of LABs, recovered from drupes of olive oil varieties, as natural fungicides, was demonstrated. Highlights: Inhibitory activity of LABs, recovered from drupes of olive oil, was demonstrated. Strong efficacy of LABs in inhibiting the growth of various fungi and oomycetes. Antifungal activity of Streptococcus salivarum and Enterococcus faecium. Characterization of diverse phenolic acids and VOCs from isolated LABs.